POTENSI KERTAS SEBAGAI BAHAN BAKU PAPER ROPES (POTENTIAL OF PAPER AS THE RAW MATERIAL FOR PAPER ROPES) - Mungki Septian Romas; Ikhwan Pramuaji; Lies Indriati; Sonny Kurnia Wirawan (Center for Pulp and Paper, 2017)
One of the raw materials furniture common in Indonesia is rattan. Because of the availability of local rattan is very limited so that it is necessary to find alternative raw materials that can be used to substitute the rattan. Paper ropes made from spinning paper, is one of alternative that can be utilized. Paper ropes making from various spinning papers have been studied. Some types of paper were used in this experiment. The spinning papers were characterized and treated to modify its surface properties especially to increase their water resistance. Paper ropes making were done by using the twisting machine and then the physical properties of paper ropes resulted were tested. The results showed that paper surface treatment increased tensile strength, and reduced water absorption and porosity of treated papers. The use of water barrier chemicals and adhesive are effective in increasing water resistance of paper surface. Decreased water absorption and porosity are 20% - 43% and 30% - 98%, respectively. Based on this result, paper ropes is potential to become an alternative raw material for furniture. ABSTRAKSalah satu bahan baku furnitur umum di Indonesia adalah rotan. Karena ketersediaan rotan lokal sangat terbatas sehingga diperlukan untuk mencari bahan baku alternatif yang dapat digunakan untuk menggantikan rotan. Paper ropes yang terbuat dari spinning paper, merupakan salah satu alternatif yang dapat dimanfaatkan. Pembuatan paper ropes dari berbagai jenis spinning paper telah dipelajari pada penelitian ini. Beberapa jenis kertas digunakan dalam percobaan ini. Spinning paper dikarakterisasi dan diperlakukan khusus untuk memodifikasi sifat permukaannya terutama untuk meningkatkan ketahanan airnya. Pembuatan paper ropes dilakukan dengan menggunakan mesin pemilin dan pengujian sifat fisik paper ropes telah dilakukan. Hasil penelitian menunjukkan bahwa perlakuan khusus permukaan kertas meningkatkan kekuatan tarik, dan mengurangi penyerapan air dan porositas. Penggunaan bahan kimia water barrier dan adhesif cukup efektif dalam meningkatkan ketahanan air permukaan kertas. Penurunan penyerapan air dan porositas masing-masing sebesar 20% - 43% dan 30% - 98%. Berdasarkan hasil ini, paper ropes memiliki potensi sebagai bahan bahan baku alternatif untuk furnitur.